Nurses’ perspectives on emergency room healthcare constraints in implementing family-centered care: A qualitative study in Indonesia - Rakhmawati, Windy; Mufida; Mediani, Henny Suzana; Fitri, Siti Yuyun Rahayu; Mardhiyah, Ai; Rhamelani, Putri (Belitung Nursing Journal, 2026)
Background: Children with acute conditions that suddenly worsen need immediate care in the Emergency Room (ER). Family-Centered Care (FCC) is considered the best approach in pediatric nursing, but its implementation in the ER is still limited. This is due to various challenges that can increase child and family anxiety and decrease the quality of nursing care. Objective: This study aimed to explore nurses’ perspectives on the constraints of the health service system in implementing FCC in child care in the ER. Methods: The study used a qualitative descriptive design. Eleven nurses working in the ER at Mokopido Tolitoli Regional Hospital participated in the study, which were chosen through purposive sampling. Data were collected using semi-structured interviews conducted from July 11 to July 23, 2023. Data were analyzed manually using a thematic approach. Results: The thematic analysis revealed two main interrelated themes regarding barriers to FCC in the ER: human resource constraints and organizational constraints. Human resource constraints include limited nursing staff, varying educational levels, lack of training or outreach on FCC, lack of competency, and communication barriers. Meanwhile, organizational constraints include high ER workloads, limited nurse time, and a focus on emergency medical procedures rather than a holistic approach. These various barriers lead to suboptimal family involvement in the care of children in the ER. Conclusion: The implementation of FCC in the ER still faces major challenges. These findings highlight the need for a strategic approach and supportive policies to improve nurse capacity and foster a collaborative and responsive hospital environment for patients’ families.